[18F]Fluoroalkyl azides for rapid radiolabeling and (Re)investigation of their potential towards in vivo click chemistry. Issue 28 (5th July 2017) - Denk, Christoph; Wilkovitsch, Martin; Skrinjar, Philipp; Svatunek, Dennis; Mairinger, Severin; Kuntner, Claudia; Filip, Thomas; Fröhlich, Johannes; Wanek, Thomas; Mikula, Hannes
Abstract : [ 18 F]Fluoroalkyl azides were developed as efficient click agents for rapid radiolabeling, and (re)investigated towards application in pretargeted PET imaging. Abstract : In recent years, radiofluorinated alkyl azides have been reported for click radiolabeling and pretargeted PET imaging, but only little is known about the biodistribution and metabolism of these compounds. In this work, we present a significantly improved procedure for the synthesis of [ 18 F]fluoroethyl azide and reinvestigated this radiolabeled probe in detail showing poor stability and very restricted suitability for in vivo application. Therefore, modified low-molecular-weight [ 18 F]fluoroalkyl azides were developed. Propargyl-tagged endomorphin-1 (as model compound) was successfully radiolabeled in high yield and short reaction time making these probes useful and efficient bioorthogonal tools for rapid radiolabeling. Biodistribution, pharmacokinetics and in vivo stability were studied by preclinical PET/MR scanning and metabolite analysis. The results of this study revealed only limited applicability of [ 18 F]fluoroalkyl azides for in vivo application.